Empire of the air : the men who made radio - Lewis, Tom, 1942- (Ithaca [New York] : Cornell University Press, 2021)
"Biography of 3 Americans, Lee de Forest, Howard Armstrong, and David Sarnoff, who turned a hobbyists' toy into radio, and launch the modern communications age. The narrative of their creations is punctuated by acts of idealism and imagination, greed and envy, ambition and determination--and genius. It covers 1899 to 1954"--
A New empire for a new century -- The faith in the future -- The will to succeed -- "What wireless is yet to be" -- Sarnoff and Marconi: inventing a legend -- Wireless goes to war -- Releasing the art: the creation of RCA -- Snapshots from the first age of broadcasting -- Court fight -- The godlike presence -- Armstrong and the FM revolution -- The wizard war -- "Until I'm dead or broke" -- Victories great and small -- The empire in decline.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 23, 2021).
JSTOR
Keywords: De Forest, Lee, -- 1873-1961.; Armstrong, Edwin H. -- 1890-1954.; Sarnoff, David, -- 1891-1971.; Sarnoff, David, -- 1891-1971.; Armstrong, Edwin H. -- 1890-1954.; De Forest, Lee, -- 1873-1961.; Armstrong, Edwin H. -- 1890-1954; De Forest, Lee, -- 1873-1961; Sarnoff, David, -- 1891-1971; Radio -- United States -- History; Radio -- United States -- Biography; TECHNOLOGY & ENGINEERING / Radio; Radio; United States; Biography; Biographies; History; Biographies; Biographies